The Cosmopolitical Applications of the “Spiritual” in Animist Cultures and their relevance to the environmental humanities today - Bennett, Fionn (Das Questões, 2021)
Through a critical reading of Bruno Latour’s "cosmopolitics“ this paper maintains that the "animist" acceptation of the “the spiritual” can be repurposed into a valuable mediating resource between humankind and the beleaguered planet we live upon. By adopting a “consequentialist standpoint” it assesses the “instrumental value” of the spiritual as a means to foster improved Man-Nature relations. In this assessment I focus on the way “animist cultures” tend to regard the natural environment as sentient and "besouled“ and the way this inclines them to avoid abusing their fellow creatures. I also conside r how they interacted with their environment for productivistic and consumeristic purposes while simultaneously venerating it. Finally, I show how animists submit both humankind and its non human Other to a "cosmodicy“ which constrains both to relate to and interact with one other on an “I Thou” basis, thereby facilitating dialogue and an "entente cordiale" between humanity and nature.